Spread the Magic: Second Grade Students Engage with the Community. Issue 2 (4th March 2019) - Morris, Ronald V.
Abstract: Second grade students learn about philanthropy by creating projects where they work through an inquiry process. Each student works with a group to create community-based projects that support existing local non-profits to enrich the quality of life in an area. Student action is visible through an authentic assessment event that allows students to showcase their achievements in front of the extended school community. The event demonstrates that students participate in civic education at a developmentally appropriate level. Teachers work within a yearlong theme to help students learn civic participation.